A Highly Sensitive Two-Dimensional Inclinometer Based on Two Etched Chirped-Fiber-Grating Arrays - Hung-Ying Chang; Yu-Chung Chang; Wen-Fung Liu (Sensors, 2017)
We present a novel two-dimensional fiber-optic inclinometer with high sensitivity by crisscrossing two etched chirped fiber Bragg gratings (CFBG) arrays. Each array is composed of two symmetrically-arranged CFBGs. By etching away most of the claddings of the CFBGs to expose the evanescent wave, the reflection spectra are highly sensitive to the surrounding index change. When we immerse only part of the CFBG in liquid, the effective index difference induces a superposition peak in the refection spectrum. By interrogating the peak wavelengths of the CFBGs, we can deduce the tilt angle and direction simultaneously. The inclinometer has a resolution of 0.003° in tilt angle measurement and 0.00187 rad in tilt direction measurement. Due to the unique sensing mechanism, the sensor is temperature insensitive. This sensor can be useful in long term continuous monitoring of inclination or in real-time feedback control of tilt angles, especially in harsh environments with violent temperature variation.